2015
DOI: 10.1097/ccm.0000000000001133
|View full text |Cite
|
Sign up to set email alerts
|

County-Level Effects of Prehospital Regionalization of Critically Ill Patients

Abstract: Objective Regionalization may improve critical care delivery, yet stakeholders cite concerns about its feasibility. We sought to determine the operational effects of prehospital regionalization of non-trauma, non-arrest critical illness. Design Discrete event simulation study Patients and setting All 2006 hospital discharge data from King County, Washington, linked to all adult, eligible patients transported by county EMS agencies. Methods We simulated active triage of high-risk patients to designated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…At the same time, intensive care expansion in the largest hospitals may have unintended consequences, such as reduced quality in small hospitals that lose their critical care capacity (12) and reduced geographic access in regions served by smaller hospitals (13, 14). In silico simulation studies reveal that the former may be less of concern (15), but the relationship between regionalization and reduced quality at small hospitals awaits empiric investigation. There is recent evidence that intensive care provides measureable benefits to the marginal patient (16), making future research to understand the clinical implications of this expansion and centralization ever more relevant in the current health care landscape (17).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, intensive care expansion in the largest hospitals may have unintended consequences, such as reduced quality in small hospitals that lose their critical care capacity (12) and reduced geographic access in regions served by smaller hospitals (13, 14). In silico simulation studies reveal that the former may be less of concern (15), but the relationship between regionalization and reduced quality at small hospitals awaits empiric investigation. There is recent evidence that intensive care provides measureable benefits to the marginal patient (16), making future research to understand the clinical implications of this expansion and centralization ever more relevant in the current health care landscape (17).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a simulated study of non-trauma, nonarrest critical illness, Seymour et al(46) demonstrated that prehospital regionalization does not drastically increase travel times, overburden referral center ICUs, or deplete non-referral hospitals. Although simulation models suggest that healthcare systems may not bear strain from inter-hospital transfers, studies are needed to identify changes in patient severity of illness and evolution of organ dysfunction during the process of inter-hospital transfer.…”
Section: Discussionmentioning
confidence: 99%
“…This prehospital risk score complements these condition-specific tools by functioning as a “score for all” among a heterogeneous group of prehospital encounters, and it could be considered for prospective validation. Additional barriers limit regionalization demonstration projects, including uncertainty over which regions to centralize, lack of stakeholder consensus, and the potential impact of new referral patterns on the financial stability of hospitals and healthcare systems [ 24 ]. These challenges will be more feasible to address with a validated triage tool, and careful study of stakeholders’ perspectives on patient referrals and the financial effects of regionalization will be necessary prior to and during any demonstration projects.…”
Section: Discussionmentioning
confidence: 99%